KONFLIK MASYARAKAT DENGAN PT RIMBA ROKAN LESTARI (RRL) DI KECAMATAN BANTAN KABUPATEN BENGKALIS - ", Suryadi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Bantan District of Bengkalis, covering five villages, Bantan Timur Village, Bantan Sari Village, Bantar Air Village, Bantan Tengah Village and Ulu Island Village. As for the problems to be investigated in this conflict, firstly, what are the factors causing community conflict with PT RRL in Bantan District ? Second, how is the community effort to reject PT RRL?This research is descriptive qualitative research. The subjects in this study were the people who were directly involved in the turmoil when PT RRL began to socialize and claim their land which has obtained permission from the Minister of Forestry. In addition, some stakeholders or agencies responsible for this conflict are also subject to research, in order to obtain data or documents that support the research. Among them, Camat Bantan, Plantation Service and Forestry Bengkalis, the Special Committee of Monitoring and Identification of Land and Plantation Land Disputes in Bengkalis Regency approved by the Chairman of DPRD Bengkalis.Techniques used in non probability with snowball method. That is, information is obtained in a chain from one resource to another interrelated resource. To collect data and verify the information obtained, also conducted observation, documentation and interviews face to face.From the results of the study it can be concluded that the factors causing community conflict with PT RRL is about land ownership. The community controlled the land long before the republic was established compared to PT RRL licensed in 1998. With this conflict the land owner community seeks to keep PT RRL from operating on the land they manage. The effort was made by forming a group which they called the bengkalis-bantan aliansi rejected PT RRL, urging the legislative members and the District Government of Bengkalis , in order to recommend the revocation of PT RRL.Keywords: Alliance, PT RRL, conflict, land